Literature Review: Hubungan Hasil Disiplin Belalajar dan Motivasi Belajar terhadap Hasil Belajar Siswa - Rahmi, Aulia; Alberida, Heffi (Lembaga Yasin AlSys, 2024)
Learning outcomes are things that determine whether learning occurs well or not. These learning outcomes are not only influenced by the environment but also influenced by oneself or internal factors. Examples of internal factors that influence student learning outcomes are learning discipline and learning motivation. The relationship between learning discipline and learning motivation on learning outcomes can be assessed by means of a correlation test. In this article we will discuss the results of previous research regarding the relationship between discipline, motivation and learning outcomes. How big is the correlation between discipline and motivation on learning outcomes. Based on the research results described previously, it can be concluded that there is a positive and significant relationship between learning discipline and learning motivation on student learning outcomes.